2020
DOI: 10.1007/s13691-020-00444-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric glomus tumor with a preoperative diagnosis by endoscopic ultrasonography-guided fine needle aspiration: a case report

Abstract: A gastric glomus tumor (GGT) is a rare gastric submucosal tumor that can become malignant. A preoperative diagnosis would allow for a more informed decision regarding the treatment strategy. We present the case of an asymptomatic man with a GGT that was diagnosed during a preoperative examination. Upper gastrointestinal endoscopy was performed in a 64-yearold man and revealed a submucosal tumor at the lesser curvature of the antrum of the stomach. Endoscopic ultrasonography showed a 12-mm-sized hypoechoic tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
(14 reference statements)
0
11
0
1
Order By: Relevance
“…In a review of 14 cases of gastric glomus tumors, 2,6,13,17–24 inclusive of our two cases, the cytomorphology of the cells from EUS‐FNA most often appeared as round to oval in shape, and uniform in appearance with clear to eosinophilic cytoplasm, fine chromatin, and inconspicuous nucleoli (Table 1). All 12 cases reported that the immunostains demonstrated positive alpha‐smooth muscle actin (SMA) expression, which helped support the diagnosis of glomus tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of 14 cases of gastric glomus tumors, 2,6,13,17–24 inclusive of our two cases, the cytomorphology of the cells from EUS‐FNA most often appeared as round to oval in shape, and uniform in appearance with clear to eosinophilic cytoplasm, fine chromatin, and inconspicuous nucleoli (Table 1). All 12 cases reported that the immunostains demonstrated positive alpha‐smooth muscle actin (SMA) expression, which helped support the diagnosis of glomus tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, 46 cases of gastric glomus tumor were reported in the literature between 2010 and 2019, and only 19 of them had a preoperative diagnosis. Among the patients who underwent endoscopic ultrasound-guided fine-needle aspiration to determine the pathology, a diagnosis was correctly given in only 8 out of 13 cases [ 13 ]. Although EUS-guided biopsy has been reported to be able to provide an accurate diagnosis in some cases, resection might be a more favorable alternative for both diagnosis and treatment [ 4 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tais estruturas estão envolvidas principalmente na regulação da temperatura central e na homeostase, consistindo num shunt arteriovenoso (o canal Sucquet-Hoyer) (Bai, et al, 2021;Chabowski, et al, 2016;Gupta, et al, 2020;Tantia, et al, 2021;Vig, et al, 2017). Esta lesão no sistema gástrico foi primeiramente descrita em 1951 por Kay e colaboradores, e hoje representa aproximadamente 1 % de todas as neoplasias mesenquimais gástricas que surgem na submucosa e na muscular própria (Alsahwan, et al, 2021;Aoba, et al, 2018;Hasuda, et al, 2021;Xing, et al, 2022).…”
Section: Discussionunclassified